2011
DOI: 10.12659/msm.881843
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the instantaneous inward rectifier and the delayed outward rectifier potassium channels by Captopril and Angiotensin II via the Phosphoinositide-3 kinase pathway in volume-overload-induced hypertrophied cardiac myocytes

Abstract: SummaryBackgroundEarly development of cardiac hypertrophy may be beneficial but sustained hypertrophic activation leads to myocardial dysfunction. Regulation of the repolarizing currents can be modulated by the activation of humoral factors, such as angiotensin II (ANG II) through protein kinases. The aim of this work is to assess the regulation of IK and IK1 by ANG II through the PI3-K pathway in hypertrophied ventricular myocytes.Material/MethodsCardiac eccentric hypertrophy was induced through volume-overlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…The present data confirms previous studies [20] demonstrating that AngII may down regulate the PI3K pathway in the hypertrophied heart model. Alvin and col., 2011 showed that PI3-kinase inhibition negated the AngII-dependent increase in L-type calcium channel current density during the development of volume overload-induced cardiac hypertrophy.…”
Section: Figuresupporting
confidence: 93%
“…The present data confirms previous studies [20] demonstrating that AngII may down regulate the PI3K pathway in the hypertrophied heart model. Alvin and col., 2011 showed that PI3-kinase inhibition negated the AngII-dependent increase in L-type calcium channel current density during the development of volume overload-induced cardiac hypertrophy.…”
Section: Figuresupporting
confidence: 93%